Comparative morphological characteristics of helicobacter pylori and autoimmune gastritis - N. V. Pachuashvili; D. P. Nagornaya; A. S. Tertychnyy (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Objective: to conduct a comparative morphological analysis of helicobacter pylori (H. pylori) and autoimmune gastritis and to determine the significant morphological criteria for differential diagnosis.Materials and methods. 30 cases of chronic atrophic helicobacter gastritis and 30 cases of chronic atrophic autoimmune gastritis were retrospectively selected for the study. In all cases of helicobacter gastritis, the presence of H. pylori was confirmed by morphological diagnostic methods using Giemsa staining or additionally using immunohistochemistry. All cases of autoimmune gastritis were additionally confirmed by clinical and laboratory diagnostic methods, some patients had a long history of follow-up and biopsy material was taken from them repeatedly. A prerequisite was taking at least 5 biopsies according to the Sydney Protocol.Results. The main differential diagnostic feature in our study was the detection of H. pylori, as well as the localization of the lesion in the stomach body characteristic of autoimmune gastritis and in the antrum in helicobacter gastritis. The study groups differed by gender (the predominance of females in the group of autoimmune gastritis), the prevalence and activity of inflammation (all cases of helicobacter gastritis had signs of inflammation activity). When studying the content of neuroendocrine cells in cases of helicobacter gastritis in the stomach body, simple hyperplasia of neuroendocrine cells was noted, in cases of autoimmune gastritis, the appearance of chains and nodules was noted, which corresponded to linear and nodular hyperplasia of neuroendocrine cells.Conclusion. The morphological criteria obtained in the study make it possible to make a differential diagnosis between helicobacter and autoimmune gastritis. This is extremely important because of the differences in treatment approaches and dynamic monitoring tactics in these variants of chronic gastritis.